CONTINUOUS IMPLEMENTATION OF CRIMINAL LAW FOR PERPETRATORS OF SEXUAL VIOLENCE AGAINST CHILDREN (STUDY OF DECISION NUMBER 670/PID.SUS/2022/PN KIS) - Maya Jannah; Kusno Kusno; Muhammad Khairul Ritonga; Nur Hikmah; Putri Habibah Siregar (Universitas Labuhanbatu, 2024)
This study aims to find out about the Continuous Implementation of Criminal Law for Perpetrators of Sexual Violence Against Children (Study of Decision Number: 670/PID.SUS/2022/PN KIS). This study is expected to help us understand how the application of criminal law for perpetrators of sexual violence is continuously applied to children as victims of sexual violence, so that the public can understand whether or not the application of criminal penalties for perpetrators of crimes is in accordance with applicable laws and regulations. This study uses a normative legal method and uses a type of legislative approach, and case studies. The type of data used is secondary data. Discussion Results: The Continuous Implementation of Criminal Law for Perpetrators of Sexual Violence Against Children based on Decision Number: 670/PID.SUS/2022/PN KIS is in accordance with what applies in the Law of the Republic of Indonesia Number. 23 of 2002 as amended by Law No. 35 of 2014 concerning Child Protection in conjunction with Article 64 paragraph (1) of the Criminal Code which states: “If several acts constitute a crime or violation and are related, then only one criminal rule shall be applied. And if the criminal rules are different, then the criminal rule with the most severe principal criminal threat shall be applied.”Keywords: Implementation, Criminal Law, Perpetrators, Sexual Violence, Continuously, Children